2021
DOI: 10.1093/rpd/ncab171
|View full text |Cite
|
Sign up to set email alerts
|

Chest Ct Usage in Covid-19 Pneumonia: Multicenter Study on Radiation Doses and Diagnostic Quality in Brazil

Abstract: We assessed variations in chest CT usage, radiation dose and image quality in COVID-19 pneumonia. Our study included all chest CT exams performed in 533 patients from 6 healthcare sites from Brazil. We recorded patients’ age, gender and body weight and the information number of CT exams per patient, scan parameters and radiation doses (volume CT dose index—CTDIvol and dose length product—DLP). Six radiologists assessed all chest CT exams for the type of pulmonary findings and classified CT appearance of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A Brazilian multicenter study reported CTDIvol and DLP median values (interquartiles range) of 10 (4) mGy and 367 (166) mGy cm and 9 (4) mGy and 298 (140) mGy cm for male and female patients, respectively. Since a routine, non-contrast chest CT protocol (standard protocol) was used in all healthcare centers, and since that included different types of scanners, it is understandable that dose descriptors were higher in comparison to ours [ 36 ]. A study focusing on 15 pregnant women who had pneumonia as a result of COVID-19 disease reported values for CTDI vol , mean values of 4.1 mGy and a range of 2.3–5.8 mGy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian multicenter study reported CTDIvol and DLP median values (interquartiles range) of 10 (4) mGy and 367 (166) mGy cm and 9 (4) mGy and 298 (140) mGy cm for male and female patients, respectively. Since a routine, non-contrast chest CT protocol (standard protocol) was used in all healthcare centers, and since that included different types of scanners, it is understandable that dose descriptors were higher in comparison to ours [ 36 ]. A study focusing on 15 pregnant women who had pneumonia as a result of COVID-19 disease reported values for CTDI vol , mean values of 4.1 mGy and a range of 2.3–5.8 mGy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Andrea et al (68) and Niu et al (69) recognized that a low radiation dose could still provide sufficient diagnostic quality to exclude COVID-19. Bernardo et al (70) deemed that there was little difference in the distribution and lobar extent of pulmonary lesions on chest CT despite substantial differences in CT usage. Moreover, the CT images included in the articles were read by two or more senior radiologists with a host of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation doses are linked to image quality, and the specific clinical indication or motive should dictate the quality of the image. Therefore, the monitoring of radiation doses must involve documentation and analysis of the clinical indications or reasons for scanning ( 4 , 5 ) . With the technological revolution proceeding at an exponential pace, most scanners can automatically adapt radiation doses and maintain quality for different body parts and patient sizes.…”
Section: Radiation Dose Descriptorsmentioning
confidence: 99%